Intraocular pressure : the effect of short-term fasting and its association with fluid and fat status - Esa, Nur Raihan; Mohd Shukri, Nor Azwani; Ahmad, Norsham; Hilmi, Mohd Radzi; Md Mustafa, Md Muziman Syah; Ibrahim, Nura Syahiera; Che Arif, Fatin Amalina; Yusof @ Alias, Firdaus (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Introduction: Short-term fasting may influence intraocular pressure (IOP) due to alteration of fluid (total body water; TBW, and water intake) and fat (total body fat; TBF). This study aimed: i) to compare IOP values within and between, fasting and non-fasting periods; and ii) to assess the association between IOP and, TBW and TBF. Methods: Thirty healthy participants aged 21.8±1.1 years were assessed on two different periods (fasting vs. non-fasting). During each period, the IOP, TBW and TBF values were assessed for four times (morning, afternoon, evening, late-evening). The IOP was measured using AccuPen® tonopen, while TBW and TBF were assessed by using a Tanita body composition analyser. Results: During fasting, the IOP value in the afternoon (14.53±2.33 mmHg) was significantly higher than in the evening (12.43±2.73 mmHg, p=0.009) and late-evening (12.60±2.44 mmHg, p=0.003). No significant difference in IOP was observed during non-fasting period. The mean of IOP in the evening was significantly lower during fasting compared to non-fasting (12.43±2.73 mmHg vs 13.75±2.53 mmHg, p=0.044). The IOP and TBW were negatively correlated (r=-0.268; p=0.011) during non-fasting and showed no association during fasting period. There was no significant correlation between IOP and TBF during both fasting and non-fasting periods. Conclusion: IOP reduction during short-term fasting, together with the no association with TBF and TBW suggested that IOP is an independent factor that reduces during fasting in healthy population.